Adjunctive use of Angio-Seal closure device following transcatheter aortic valve implantation via percutaneous transfemoral approach with incomplete hemostasis after modified Perclose ProGlide preclosure technique. Issue 1 (2nd January 2019) - Fan, Jerry; Lane, Wesley; Lawrence, Mark; Mixon, Timothy
Abstract: Adequate and reliable hemostasis following transcatheter aortic valve implantation (TAVI) is crucial. Closure devices have improved the amount of time required to achieve hemostasis following these procedures. We retrospectively looked at TAVI procedures that achieved adequate hemostasis after use of the Angio-Seal as an adjunctive measure following use of the Perclose ProGlide system. Sixteen cases (age range, 56–91 years) were identified between January 2016 and February 2018. Half had undergone transfemoral diagnostic angiography in the same vessel used for the TAVI delivery system within the prior 1 to 63 days. Five were receiving oral anticoagulants; six, aspirin; and two, dual-antiplatelet therapy. All had undergone computed tomography angiography for sizing of iliofemoral arteries, aorta, and the aortic valve prior to TAVI. No patient experienced any significant access site-related complications or ischemic leg symptoms, and there were no reports of late vascular or access site complications. Our case series suggests that adjunctive Angio-Seal systems may be a reliable alternative for incomplete hemostasis following Perclose ProGlide systems and can serve as a "bailout" procedure for incomplete postprocedural hemostasis.